The interface of the universal: On Hegel’s concept of the police - Kobe Zdravko (Filozofija i Društvo, 2019)
The article provides a tentative reading of Hegel’s police as a concept that constitutes a crucial test for the rationality of Hegel’s state and that actually played a very important role in the formation of his model of rationality. It starts by considering some significant changes in Hegel’s approach to the subject in the Jena period, especially in reference to Fichte and Spinoza; then, it presents Hegel’s conception of the police as the interface of the universal in his mature political philosophy, together with his treatment of the disturbing problem of poverty and the rabble; and to conclude, it adds some general remarks on Hegel’s police, then and now.